PERSEPSI MAHASISWA ATAS KUALITAS PELAYANAN DAN PROMOSI TERHADAP MINAT MENGGUNAKAN AKAD WADIAH DI BANK SYARIAH - Ellisa Nur Amelia (2021)
Users of wadiah savings accounts are more desirable in Islamic banks, this can be seen from the high number of wadiah savings accounts in the financing data and third party funds of Islamic commercial banks in Islamic Banking Statistics 2020. The increase in users of wadiah savings accounts occupies 1.2%, which is superior compared to mudharabah contract savings. This study aims to determine student perceptions of service quality and promotion of interest in using wadiah contracts in Islamic banks. This analysis uses independent variables, namely service quality and promotion. The dependent variable is interest. The sample of this research is students who have savings at Bank Syariah Mandri, Bank Negara Indonesia Syariah and Bank Rakyat Indonesia Syariah. Data was collected by using a questionnaire distributed directly as many as 100 questionnaires. The method used in this study is multiple linear regression analysis, with hypothesis testing t test and f test. The results of this study indicate that service quality has a significant positive effect on interest, while promotion has a positive but not significant effect on interest. For service quality and promotion together have a significant positive effect on interest. The results of this study in the future contribute to the increase in Islamic bank customers through the use of wadiah contracts with good service quality and good promotions created.